Perspective tomato landraces for fresh consumption in the Republic of North Macedonia - Gordana Popsimonova; Rukie Agic; Zvezda Bogevska; Davitkovska, Margarita; Goce Georgievski (My University, 2020)
Following long pepper, tomato is most widely cultivated vegetable in the Republic of Macedonia. It is mainly grown under tunnels and in glasshouses. Considerable portion of the production is intended for export during April, May and June, whereas the local markets are supplied with imports for the rest of the year. A survey has been carried out at the beginning of 2016 aiming to determine consumer preferences for fresh tomato among 50 fresh markets and distributors. It was concluded that consumers prefer to buy local landraces over hybrids. Landrace with apple shaped tomato fruit (Yabuchar) is favorite one for the buyers. In order to enrich the offer of the local tomato producers, 10 Yabuchar-type tomato landraces, collected from different villages and producers during 2016 have been tested for their productive and qualitative traits. Field trials were carried out in the villages of Drachevo and Lisiche, both in vicinity of the capital, Skopje. The landraces were grown in open field conditions following standard agricultural practices for this type of tomato. The characterization of the examined landraces was made by IPGR descriptor for tomato (Lycopersiocon esculentum Mill.). Although all these landraces appear under the same name, significant distinctiveness has been recorded regarding morphological traits such as flower morphology, shape and size of the fruits, pericarp thickness, cracking and green zone of the fruits and mass of the fruits, as well as in the content of sugars. Main drawback for wider production of these landraces is generally short shelf live that might be improved in further breeding programs.
Keywords: tomato, landraces, morphological traits, fruit quality